Power in the Multinational Corporation in Industry Equilibrium - Dalia Marin; Thierry Verdier (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2007)
Recent theories of the multinational corporation introduce the property rights model of the firm and examine whether to integrate our outsource firm activities locally or to a foreign country. This paper focus instead on the internal organization of the multinational corporation by examining the power allocation between headquarters and subsidiaries. We provide a framework to analyse the interaction between the decision to serve the local market by exporting or FDI, market acces and the optimal mode of organization of the multinational corporation. We find that subsidiary managers are given most autonomy in their decision how to run the firm at intermediate levels of local competition. We then provide comparative statics for changes in fixed FDI entry costs and trade costs, information technology, the number of local competitors, and in the size of the local market.
urn:nbn:de:bvb:19-epub-1922-2
Keywords: D23; F1; F2; 330; foreign direct investment; power allocation in the firm; international trade and the organization of production; Multinationales Unternehmen; Export; Auslandsinvestition; Ausländische Tochtergesellschaft; Führungsorganisation; Wirtschaftsmodell